Peran Orang Tua Terhadap Penguatan Nilai-Nilai Karakter Sebagai Upaya Meningkatkan Civics Disposition Peserta Didik Di Masa Pandemi Covid-19 - Gandara, Yoga; Yohana Oktaviani Lavan; Zulkifli (Universitas Pendidikan Ganesha, 2024)
Problems regarding the formation of children's character during the COVID-19 pandemic are very important, in the midst of this condition there must be strategic handling to restore the world of education. Parents have an important role to realize the success of learning as well as changes in student behavior. The need for the main role of parents during distance learning in creating children's character is to guide or as the main role model for their children. Parents must interact interactively with schools and the community to develop educational patterns that emphasize character values ​​during the current COVID-19 pandemic. The method used in writing this article is a literature study and discourse analysis with a qualitative approach. The data collection technique used is library research. The purpose of writing this article is to increase parental awareness of strengthening character values ​​as an effort to improve children's civic character during online or distance learning during the COVID-19 pandemic.